Equivalent bronchodilation with budesonide/formoterol combination via Easyhaler and Turbuhaler in patients with asthma. (November 2016) - Lähelmä, Satu; Vahteristo, Mikko; Metev, Hristo; Taseva, Margarita; Stamatova, Nadezhda; Bartha, Anna; Schlezák, Judit; Sairanen, Ulla
Abstract: Background: Therapeutic equivalence of Budesonide/formoterol Easyhaler compared to Symbicort Turbuhaler has been previously demonstrated with in vitro and pharmacokinetic studies. This study was performed to confirm equivalent bronchodilator efficacy of the products in asthmatic patients. Methods: A randomised, single-dose, 4-period crossover study was carried out in a double-blind, double-dummy manner in 11 study sites. The studied doses were 320/9 μg and 1280/36 μg of budesonide/formoterol delivered by Easyhaler and Turbuhaler. Spirometry was performed before and 10 min, 20 min and 1, 2, 3, 4, 6, 8, 10 and 12 h after administration of the study treatments. The primary efficacy endpoint was average 12-h forced expiratory volume in 1 s (FEV1 ). The secondary efficacy endpoints were maximum FEV1 and FEV1 at 12 h post-dose. Results: 72 asthma patients with reversible airway obstruction were randomised to receive study treatments. 53 patients completed all study periods according to the protocol and had sufficient data available to calculate the primary endpoint. They were included in the per-protocol analyses. The assay sensitivity of the study was shown as the common slope of average 12-h FEV1 between doses was 0.063 (95% CI 0.032–0.093) and showed statistical significance (p < 0.001). In equivalence testing, the difference in average 12-h FEV1 between the treatments (Easyhaler-Turbuhaler) was 0.013 l at the lower dose and −0.028 l at the higher dose, and their 95% confidence intervals (CIs) (−0.047 to 0.073 and −0.087 to 0.032, respectively) fell within the range of a clinically non-relevant difference. The results of the secondary efficacy endpoints were in line with the results of the primary endpoint. All treatments were well tolerated. Conclusions: The results confirm equivalent bronchodilator efficacy of Budesonide/formoterol Easyhaler compared to Symbicort Turbuhaler. Trial registration: This trial was registered onClinicalTrials.gov, Identifier:NCT02308098 . Highlights: Bronchodilation study comparing Budesonide/formoterol Easyhaler and Turbuhaler. FEV1 was measured and average 12-h FEV1 was calculated. 36 μg dose of formoterol was statistically significantly superior to 9 μg dose. Equivalence was confirmed between Easyhaler and Turbuhaler at both dose levels.